2022
DOI: 10.3389/fonc.2022.763480
|View full text |Cite
|
Sign up to set email alerts
|

La protein regulates protein expression by binding with the mRNAs of target genes and participates the pathological process of ovarian cancer

Abstract: Research on the mechanism and new targets of ovarian cancer is of great significance to reduce the high mortality and drug resistance of ovarian cancer. Human La protein has been found to be highly expressed in a variety of malignant tumors and plays a role in tumorigenesis and development through its RNA-binding function. However, its role and mechanism in ovarian cancer are not completely clear. The present study showed that La protein was highly expressed in serum and tissues of patients with ovarian cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…According to Huang et al [30], OC patients have significantly higher levels of La protein expression in their serum than healthy individuals, which is related to the poor response to platinum-based chemotherapy. Furthermore, when the expression of La interfered with La RNAi in A2780 and SKOV3 cells, its impaired cell growth, which suggests that inhibiting the overexpression of La protein could promote apoptosis and inhibits the invasion and migration of OC cells.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Huang et al [30], OC patients have significantly higher levels of La protein expression in their serum than healthy individuals, which is related to the poor response to platinum-based chemotherapy. Furthermore, when the expression of La interfered with La RNAi in A2780 and SKOV3 cells, its impaired cell growth, which suggests that inhibiting the overexpression of La protein could promote apoptosis and inhibits the invasion and migration of OC cells.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, when the expression of La interfered with La RNAi in A2780 and SKOV3 cells, its impaired cell growth, which suggests that inhibiting the overexpression of La protein could promote apoptosis and inhibits the invasion and migration of OC cells. Notably, Huang et al [30] reported the potential downstream target genes of La protein involved in the development and drug resistance of OC, including CALR, NES, PKM, RIF1, HLA-B, IGFRBP1, NQQ1, TK1, FHIT, MAP2K1, and SLC2A1. Inhibiting La protein could control the expression of these genes in impeding proliferation, invasion, migration, and chemotherapy resistance to OC [30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation